Role of Saccharomyces boulardii in diarrhea predominant irritable bowel syndrome - Kabir, MA; Ishaque, SM; Ali, MS; Mahmuduzzaman, M; Hasan, M (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):397-401 The abstract of this article is available on the PubMed website